Analisis Faktor-faktor yang Berpengaruh Terhadap Kecenderungan Kecurangan Akuntansi: Studi pada Perusahaan Publik dan Badan Usaha Milik Negara di Indonesia - WILOPO WILOPO (The Indonesian Journal of Accounting Research, 2013)
The accounting fraud is frequent, widespread and familiar in many countries and organization. It brings a loss to firms and investors. But there is no research trying to explain factors comprehensively influencing it. The objectives of the research are to test and explain the effect of the internal control effectiveness, suitability of reward, compliance to accounting rules, information asymmetry, management morality toward unethical behavior and intention to accounting fraud. More particularly, the research attempts to examine the causal relationship between the variables involved. Questionnaire was used to collect data. The analysis unit was the company. The research population was 477 companies consisting of public companies and state owned companies in Indonesia. The research samples were one hundred and fifty three companies. The research respondents were directors or managers responsible to prepare financial statements. Structural Equation Modeling was used to test the hypothesis. The findings of the research showed that internal control effectiveness, compliance to accounting rules, information asymmetry, and management morality affected unethical behavior and intention to accounting fraud significantly. But the research showed that suitability of the reward did not affect management unethical behavior and intention to accounting fraud. The findings of the study provided an input to develop comprehensive research about good governance and corruption. It is also suggested to add more comprehensive research model by adding more variables (e.g. laws, politics, and social aspects) and to develop the research in government institution and non profit organization.